Comparative analysis of the trypanocidal activity and chemical properties of E-lychnophoric acid and its derivatives using theoretical calculations - Alcântara, Antônio Flávio de Carvalho; Silveira, Damaris; Chiari, Egler; de Oliveira, Alaide Braga; Guimarães, João Edmundo; Raslan, Delio Soares (Eclética Química, 2005)
E-Lychnophoric acid 1, its derivative ester 2 and alcohol 3 killed 100% of trypomastigote blood forms of Trypanosoma cruzi at the concentrations of 13.86, 5.68, and 6.48 μg/mL, respectively. Conformational distribution calculations (AM1) of 1, 2 and 3 gave minimum energies for the conformers a, b, c, and d, which differ from each other only in the cyclononene ring geometry. Calculations (DFT/ BLYP/6-31G*) of geometry optimization and chemical properties were performed for conformers of 1, 2, and 3. The theoretical results were numerically compared to the trypanocidal activity. Calculated values of atomic charge, orbital population, and vibrational frequencies showed that the C-4–C-5 π-endocyclic bond does not affect the trypanocidal activity of the studied compounds. Nevertheless, the structure of the group at C-4 strongly influences the activity. However, the theoretical results indicated that the intra- ring (C-1 and C-9) and π-exocycle (C-8 and C-14) carbons of caryophyllene-type structures promote the trypanocidal activity of these compounds.